Assembly and dynamic operation simulation research of tooth-locked-output harmonic gear reducer. Issue 1 (1st November 2022) - Ju, Bin; Fan, Yuanxun
Abstract: Aiming at the special structure of the tooth-locked-output harmonic gear reducer, a simulation analysis method of ring shape flexspline based on ABAQUS is proposed in this paper. In the process of simulating assembly, this paper proposes a new method of "interference assembly first and then interference elimination";In the process of simulating dynamic operation, this paper uses the "Continuum Distributing" coupling function to solve the difficult problem of setting the boundary conditions of the ring shape flexspline, and completes the data transfer between the two analysis processes. The research shows that the method proposed in this paper effectively reduces the difficulty of the ring shape flexspline simulation analysis, and reduces the cost and time for subsequent research.